Identifying training needs for in-service teachers in primary education level in relation to teaching methods - al-Warfili, Faedah Imhamad Salim; Nik Mohd Rahimi Nik Yusoff,; Zamri Arifin, (2011)
This study aimed to identify training needs in-service education in the field of teaching methods for teachers of primary education at the city of Benghazi in Libya from the point of view of teachers. The study has been using the descriptive approach using the questionnaire and the qualitative methodology using the interview. The instruments was validated by expert of the field and its reliability has been approved using the Alpha Cronbach. The study found that the most important training needs of teachers from the viewpoint of the sample were training on practical methods appropriate for teaching mathematics to students, training diversify stimuli grab the attention of students,training to use the method of dumping correctly, training to link the lesson experience of pupils and their lives, training to organize the elements of the lesson steps sequesntial and logical, training on the rules of drawing, spelling and punctuation, training of the patterns of readers in silent and aloud reading for the benefit of pupils, training on the skill of the selection of teaching methods appropriate to the content of subject, and training on the use of oral questions correctly promote discussion during the teaching process.